Humans Vs. Service Robots as Social Actors in Persuasion Settings - Lee, Heekyung; Yi, Youjae (Journal of service research : JSR, 2025)
Our study departs from existing research, which primarily focuses on the benefits of automated social presence in customer service. Instead, we investigate the potential downsides of a service robot’s social presence in marketing persuasion, particularly its influence on consumers’ use of persuasion knowledge. Across five experiments, we aim to: (1) identify factors affecting the social presence of a salesclerk as a persuasion agent (type of service provider, persuasive intent, and robot appearance); and (2) reveal that anthropomorphized service robots in persuasion contexts lead to a decrease in perceived salesclerk sincerity (i.e., social presence effect), ultimately impacting consumer attitudes and behaviors. Additionally, we explore the mechanism behind the social presence effect by examining the moderating role of consumers’ dispositional persuasion knowledge. By applying the persuasion knowledge model to robot-mediated service encounters, this research offers valuable insights into the potential drawbacks of using anthropomorphic robots for marketing persuasion in service relationships. Graphical Abstract